Mental health research in Brazil: policies, infrastructure, financing and human resources - Jair de Jesus Mari; Rodrigo A Bressan; Naomar Almeida-Filho; Jerônimo Gerolin; Pratap Sharan; Shekhar Saxena (Universidade de São Paulo, 2006)
The objective of this descriptive study was to map mental health research in Brazil, providing an overview of infrastructure, financing and policies mental health research. As part of the Atlas-Research Project, a WHO initiative to map mental health research in selected low and middle-income countries, this study was carried out between 1998 and 2002. Data collection strategies included evaluation of governmental documents and sites and questionnaires sent to key professionals for providing information about the Brazilian mental health research infrastructure. In the year 2002, the total budget for Health Research was US$101 million, of which US$3.4 million (3.4) was available for Mental Health Research. The main funding sources for mental health research were found to be the São Paulo State Funding Agency (Fapesp, 53.2%) and the Ministry of Education (CAPES, 30.2%). The rate of doctors is 1.7 per 1,000 inhabitants, and the rate of psychiatrists is 2.7 per 100,000 inhabitants estimated 2000 census. In 2002, there were 53 postgraduate courses directed to mental health training in Brazil (43 in psychology, six in psychiatry, three in psychobiology and one in psychiatric nursing), with 1,775 students being trained in Brazil and 67 overseas. There were nine programs including psychiatry, neuropsychiatry, psychobiology and mental health, seven of them implemented in Southern states. During the five-year period, 186 students got a doctoral degree (37 per year) and 637 articles were published in Institute for Scientic Information (ISI)-indexed journals. The investment channeled towards postgraduate and human resource education programs, by means of grants and other forms of research support, has secured the country a modest but continuous insertion in the international knowledge production in the mental health area.